2016
DOI: 10.1126/scisignal.aaf1639
|View full text |Cite
|
Sign up to set email alerts
|

A calcium-redox feedback loop controls human monocyte immune responses: The role of ORAI Ca 2+ channels

Abstract: In phagocytes, pathogen recognition is followed by Ca(2+) mobilization and NADPH oxidase 2 (NOX2)-mediated "oxidative burst," which involves the rapid production of large amounts of reactive oxygen species (ROS). We showed that ORAI Ca(2+) channels control store-operated Ca(2+) entry, ROS production, and bacterial killing in primary human monocytes. ROS inactivate ORAI channels that lack an ORAI3 subunit. Staphylococcal infection of mice reduced the expression of the gene encoding the redox-sensitive Orai1 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(55 citation statements)
references
References 43 publications
2
53
0
Order By: Relevance
“…The positive regulation of Nox2 by TRPC3 observed in the present study suggests that there is indirect crosstalk between TRPC3 and other ROS-activated TRP channels through Nox2 activation. In phagocytes, which strongly express Nox2, sustained Ca 2+ entry through Orai1 store-operated Ca 2+ channels26 is sufficient to increase Nox2 activity in response to bacterial infection. Voltage-dependent H + channels27 also contribute to ROS production by acting to balance the charge on the membrane.…”
Section: Discussionmentioning
confidence: 99%
“…The positive regulation of Nox2 by TRPC3 observed in the present study suggests that there is indirect crosstalk between TRPC3 and other ROS-activated TRP channels through Nox2 activation. In phagocytes, which strongly express Nox2, sustained Ca 2+ entry through Orai1 store-operated Ca 2+ channels26 is sufficient to increase Nox2 activity in response to bacterial infection. Voltage-dependent H + channels27 also contribute to ROS production by acting to balance the charge on the membrane.…”
Section: Discussionmentioning
confidence: 99%
“…The ensuing Ca 2+ signals activate Nox2 at the cell surface via PKC to produce O 2 • - and H 2 O 2 as part of the oxidative burst for the killing of the pathogen. Interestingly, a switch to a redox insensitive ORAI3/ORAI1 heteromultimer was also shown to occur in monocytes following bacterial infection [228]. A higher ORAI3/ORAI1 ratio was shown to reduce the Ca 2+ amplitude [229], but resulted in a prolonged Ca 2+ signal that was not inhibited by increases in ROS [228].…”
Section: Redox Regulation Of Cellular Ca2+ Homeostasis At the Plasmentioning
confidence: 99%
“…Interestingly, a switch to a redox insensitive ORAI3/ORAI1 heteromultimer was also shown to occur in monocytes following bacterial infection [228]. A higher ORAI3/ORAI1 ratio was shown to reduce the Ca 2+ amplitude [229], but resulted in a prolonged Ca 2+ signal that was not inhibited by increases in ROS [228]. The authors proposed this to be a mechanism that ensures killing of the pathogen, but avoids extensive tissue damage in response to sustained ROS bursts.…”
Section: Redox Regulation Of Cellular Ca2+ Homeostasis At the Plasmentioning
confidence: 99%
“…; Saul et al . ). The presence of two isoforms activated by different conditions increases the diversity of cellular responses towards pathogen‐ and host‐associated ligands, cytokines, and paracrine signals, a versatility enabling neutrophils to respond to a broad range of stimuli.…”
Section: Ca2+ Signalling In Neutrophil Functionmentioning
confidence: 97%
“…STIM2 is activated by mild ER Ca 2+ -store depletion and was initially proposed to regulate basal Ca 2+ homeostasis or to act as a STIM1 inhibitor (Soboloff et al 2006;Brandman et al 2007). Recent studies, however, showed that STIM2 actively regulates SOCE in neurons, melanoma or monocytes (Berna-Erro et al 2009;Stanisz et al 2014;Saul et al 2016). The presence of two isoforms activated by different conditions increases the diversity of cellular responses towards pathogen-and host-associated ligands, cytokines, and paracrine signals, a versatility enabling neutrophils to respond to a broad range of stimuli.…”
Section: Considerations In Studying and Interpreting The Role Of Stimmentioning
confidence: 99%